Expressão protéica de VEGF, TGF-β1 e BMPR1B em tumores mamários de cadelas e sua importância no prognóstico - Silva, Robson Fernando de Pasquale e (2013)
In Brazil, mammary tumors is the most common tumor in dogs. Surgery is the treatment of choice for most cases. Histopathologic evaluation and interpretation are extremely necessary to obtain a prognosis and help the clinician decide on whether or not adjuvant treatments as well as monitor this patient. In human breast tumors evaluation by immunohistochemical markers in order to obtain more prognostic information and help to decide on specific therapies for certain types of tumors it is fundamental and critical. In veterinary medicine, little is known about markers and prognostic factors in canine mammary tumors. The Vascular Endothelial Growth factor (VEGF) is the most prevalent and most powerful factor in the process of angiogenesis, stimulating endothelial cells growth and the survivability of vessels. The Transforming Growth Factor - β (TGF-β) is well known to contribute in the control of proliferation; cell differentiation, especially as antiproliferative factor in normal epithelial cells and in the early stages of oncogenesis but can also act as promoter of tumor progression and tumor angiogenesis. The Bone Morphogenetic Protein Receptor Type 1B (BMPR1B) is also part of the great family of TGF-β and is involved in promoting and inhibiting the development of cancer. In this study these markers were used with the aim to relate mammary benign tumors, malignant mammary tumors with low / intermediate grade and high-grade lesions with quantification of immunohistochemical expression of VEGF, TGF-β1 and BMPR1B with the data obtained for each individual patient for survival time and metastasis. These neoplasms were separated into three distinct groups: Group 1 - Simple adenoma (SA), Group 2 - Simple Adenocarcinoma (SA) and lowintermediate grade (I, II,) and Group 3 – Simple Adenocarcinoma grade III or undifferentiated with skin invasion and metastasis with a clinical diagnosis of inflammatory carcinoma. The results showed that for VEGF there was no correlation between the expression in all three groups, BMPR1B was one of the markers that was obtained higher scores negative of its expression in samples of group 1, 2 and 3. The TGF-β1 in the statistical analyzes showed correlation with the degree of malignancy between group 1 and group 3 (p = 0.038). None of the three markers was associated with survival time and recurrence of tumors, at KaplanMeier construction curve method and the log rank test. The data from our study suggest that among the evaluation of the markers VEGF, TGF-β1 and BMPR1B their expression in mammary canine tumor samples by immunohistochemistry examination, the TGF-β1 was the only one that can serve as a parameter of malignancy.